3‐D tooth movement adjacent to single anterior implants and esthetic outcome. A 14‐ to 20‐year follow‐up study. Issue 11 (30th August 2021) - Winitsky, Nicole; Naimi‐Akbar, Aron; Nedelcu, Robert; Jemt, Torsten; Smedberg, Jan–Ivan
Abstract: Objectives: To report three‐dimensional (3‐D) movement of teeth adjacent to single‐implant crowns (SICs) in the anterior maxilla and to relate the findings to patient characteristics and esthetic outcome. Materials and Methods: 3‐D movements of teeth adjacent to anterior maxillary SICs were measured in 30 patients with original SICs in function after 14–20 years. The movements were related to facial type, lower anterior facial height (LAFH), age at crown delivery, sex, the position of the implant, implant occlusion, cause of tooth loss, follow‐up period, orthodontic treatment prior to implant placement, and marginal bone‐level changes. The esthetic outcome and quality were assessed using Visual Analog scale (VAS) and California Dental Association (CDA) index. Results: 3‐D movement of adjacent teeth between 0 and 2.5 mm was observed at follow‐up with incisal and palatal movement being most pronounced. Incisal tooth movement of >1 mm was observed in 30% of the patients and was significantly associated with LAFH ≥70 mm. VAS rating associated poorly between patients and clinicians with scores of >80% in 63% and 20%, respectively. The CDA rating was assessed as satisfactory in 87% of the patients. Conclusions: Significantly more extensive infraposition was observed in patients with SICs without occlusion, other causes of tooth loss than trauma, implant in lateral incisor and canine position, and a LAFH of ≥70 mm. Although infraposition occurs, patients are highly satisfied with the esthetics of their implants and the esthetic results are valued as higher by patients than dentists.